Research on the interaction mechanism between cross-regional operating enterprises and local government: perspective based on evolutionary game - Zhao, Jin; Li, Shuqi; Zhang, Jiaxin; Zhang, Linrong (Frontiers in Physics, 2025)
Against the background of a unified national market, the interaction between cross-regional operating enterprises and local governments involves factors such as investment scale, policy preferences, and industrial collaboration and has a profound impact on the innovation activities of enterprises and the improvement of regional innovation ecosystems. This study employs evolutionary game theory to construct a bilateral game model, elucidating the dynamic game–theoretic relationships between cross-regional operating enterprises and cross-entry local governments. Establishing interest interaction and government-enterprise gaming mechanisms was found to effectively promote the two sides from short-term gaming to stable cooperation and reduce strategic uncertainty. The aim is to explore in depth how cross-regional operations can further promote the improvement of innovation performance and even the high-quality development of enterprises through the strategic interaction with the governments of cross-regional places.